A clinical study of plasma homocysteine levels in chronic kidney disease at a tertiary care center - Vinay Kumar, M.; Rao, Vithal; Hussaini, Sayed Mohammed Meraj; T., Azhar Thouseef Baig (International Journal of Research in Medical Sciences, 2025)
Background: Chronic kidney disease (CKD) is associated with progressive loss of renal function and elevated plasma homocysteine levels, which may increase cardiovascular risk. This study aimed to assess the association between renal function decline and homocysteine levels in CKD patients. Methods: A single-center, prospective observational study was conducted over 18 months involving 50 CKD patients. Demographic, clinical, and biochemical data including plasma homocysteine, serum creatinine, blood urea nitrogen (BUN), urea, glomerular filtration rate (GFR), and albumin levels were collected. Patients were stratified by homocysteine levels (normal <15 µmol/l, elevated >15 µmol/l), and associations with renal parameters were analyzed. Results: Elevated homocysteine was observed in 38 (76%) patients. Patients with elevated homocysteine had significantly higher plasma homocysteine levels (21.98±7.52 µmol/l) compared to the normal group (12.22±1.83 µmol/l, p=0.001). Serum creatinine was higher in the elevated group (8.30±4.68 mg/dl) versus normal (4.68±2.17 mg/dl, p=0.001). Similarly, BUN (57.89±15.41 mg/dl versus 42.18±6.22 mg/dl, p=0.001) and urea (121.58±32.37 mg/dl versus 88.58±13.06 mg/dl, p=0.001) were elevated. The mean GFR was significantly lower in the elevated homocysteine group (11.68±6.30 ml/minute) compared to the normal group (16.44±7.93 ml/minute, p=0.03). Significant correlations were found between homocysteine and serum creatinine (r=0.305, p=0.03), BUN (r=0.335, p=0.01), urea (r=0.345, p=0.01), and GFR (r= -0.412, p=0.01). Conclusions: Elevated homocysteine levels may serve as a useful biomarker and potential therapeutic target to mitigate cardiovascular risk and disease progression in CKD.